Efektivitas Larvasida Infusa Bunga Lawang (Illicium Verum) Terhadap Mortalitas Larva Aedes Aegypti Instar III - Rahma Triyana; Thesa Andria Putri; Irma Primawati; Melya Susanti; Prima Adelin; Salmi Salmi (Malahayati Nursing Journal, 2022)
ABSTRACT Star Anise (Illicium Verum) is a plant that is widely available in Indonesia which is commonly used as a spice, flavorings in drinks, and food flavor enhancers. star anise has the potential as natural larvicides. The purpose of this research was to determine the effectiveness of larvae infusion of star anise on the mortality of Aedes Aegypti larvae. This research covers the field of parasitology, especially in the Entomology section, the research was conducted at the Biomedical Laboratory of Baiturrahmah University, Padang. The research was conducted February - March 2020, the type of research used was experimental research using the Post Test Only Control Group Design. The affordable population of this research was Aedes aegypti instar III larvae which were obtained from the results of colonization in the Health Entomology Laboratory of the Faculty of Veterinary Medicine, Bogor Agricultural University, the total sample needed is 560 larvae, data analysis using one way ANOVA test and probit test. Based on the results of infusion studies, star anise effectively kills larvae of Aedes aegypti instar III at a concentration of 32% to 100% within 24 hours, there is a comparison of the effectiveness of larvicides between the infusion of mace and commercial larvicides (abate). LC50 of larvae infusion of star anise is 7.775% and the LC99 price of larvae infusion of star anise is 53.674%. Evidently, there is a comparison of the effectiveness of larvicides between the infusion of star anise with commercial larvicides (abate). sig 0,0000.05. key words : Aedes Aegypti Larvae, Star Anise Infusion, LC50, LC99 ABSTRAK Bunga Lawang (Illicium verum) merupakan tumbuhan yang banyak terdapat di Indonesia yang biasa digunakan sebagai bumbu rempah, perisa dalam minuman dan penambah cita rasa masakan. Bunga lawang berpotensi sebagai larvasida alami. Tujuan penelitian ini untuk mengetahui efektivitas larvasida infusa bunga lawang terhadap mortalitas larva Aedes Aegypti. Penelitian ini mencakup bidang ilmu parasitologi khususnya pada bagian Entomologi, penelitian dilakukan di Laboratorium Biomedik Universitas Baiturrahmah Padang. Jenis penelitian yang digunakan adalah penelitian eksperimental dengan menggunakan rancangan Post Test Only Control Group Design, Populasi terjangkau penelitian ini adalah larva Aedes aegypti instar III yang di dapat dari hasil kolonisasi di Laboratorium Entomologi Kesehatan Fakultas Kedokteran Hewan Institut Pertanian Bogor, total sampel yang dibutuhkan adalah 560 ekor larva, analisa data menggunakan uji one way anova dan uji probit. Berdasarkan hasil penelitian Infusa bunga lawang efektif membunuh larva Aedes aegypti instar III pada konsentrasi 32% sebanyak 100% dalam waktu 24 jam. Terdapat perbedaan efektivitas larvasida antara infusa bunga lawang dengan larvasida komersil (abate). LC50 dari larvasida infusa bunga lawang adalah 7,775% dan harga LC99 dari larvasida infusa bunga lawang adalah 53,694%. Kata kunci: Larva Aedes Aegypti, infusa bunga lawang, LC50, LC99